One-step depositing method of PAni/MnO2 composites for enhanced supercapacitor performance - Shuang Xi; Xiaoli Qian; Ximing Cheng; Huilong Liu; Homa Shabanzadeh; Davoud Dastan (iScience)
Summary: Manganese dioxide (MnO2) is extensively used in supercapacitors, but its poor conductivity and low power density limit its applications. This study employed a one-step electrochemical deposition method to fabricate a polyaniline (PAni)/MnO2/carbon cloth (CC) composite electrode, which was assembled into flexible supercapacitors. Optimal process parameters were determined through exploring the effect of deposition durations on the electrochemical performance. With optimized synergistic effects between the components, the PAni/MnO2@CC composite electrode exhibits high specific capacitance of 1,694.25 mF cm−2 at 1 mA cm−2, which is remarkably better than that of PAni@CC, MnO2@CC, and other reported PAni-based electrodes. The assembled supercapacitor displays high energy density, superior bending performance, and good cycle stability. This easy-to-prepare composite electrode, with excellent energy storage capability, offers significant potential for flexible energy storage devices.